BAKING QUALITY OF SPRING SOFT WHEAT AND TRITICALE DEPENDING ON THE FORECROP AND BACKGROUND OF CULTIVATION (Experimental biology, 2021)
The article presents data on the assessment of the baking quality of the varieties of spring soft wheat - Shortandinskaya 95 improved and spring triticale – Rosinka. The purpose of the work: a comparative assessment of bread quality made from spring wheat flour and spring triticale, depending on the forecrop and background of cultivation in Northern Kazakhstan. The sowing was carried out in the period 2018-2019 on the experimental areas of the “SPC GF named after A. I. Barayev” LLP. The influence of organic and traditional farming systems on the quality of the resulting products was studied. The organic farming system included the use of aboveground biomass of perennial grasses and legumes as organic fertilizer. Traditional - the use of mineral fertilizers: ammophos in a dose of P40, ammonium nitrate in a dose of N20, N40, N60 and N80. The test baking was carried out by the non-paired method with intensive kneading of the dough using dry yeast and 100 g of flour. The evaluation of the baking advantages of flour was carried out according to the method of the state variety testing with the determination of external  and internal signs of bread quality. Based on all the indicators, the overall baking score was obtained. It was found that the baking score of triticale bread is lower than that of wheat by 1- 1.5 points. In the years of research, the dependence of the quality of bread on the predecessor and the background of cultivation was noted. The advantage for the studied crops was the organic background, the best precursor for spring triticale was melilot, for spring soft wheat – granary.
Keywords: soft wheat; bread volume; organic backgrounds; forecrop; traditional backgrounds; triticale; baking grade